Answer:
12
Step-by-step explanation:
x/2+4=10
-4 -4
________
x/2=6
(2/1)*(x/2)=(2/1)*(6)
________
x=12
The problem seems confusing is it supposed to say y=?
The formula for the average value of a function is

where b is the upper bound and a is the lower. For us, this formula will be filled in accordingly.

. We will integrate that now:
![\frac{1}{2}[ \frac{2x^3}{3}+3x]](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%7D%5B%20%5Cfrac%7B2x%5E3%7D%7B3%7D%2B3x%5D%20%20)
from 0 to 2. Filling in our upper and lower bounds we have
![\frac{1}{2}[( \frac{2(2^3)}{3}+3(2))-0]](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%7D%5B%28%20%5Cfrac%7B2%282%5E3%29%7D%7B3%7D%2B3%282%29%29-0%5D%20%20)
which simplifies to

and

which is 17/3 or 5.667